Analisis Work-Life Balance Dan Work-Life Analysis Terhadap Kinerja Karyawan Bagian Distributor Bagian Check-In Dan Check-Out Shipping Pada PT. AAA - Melia Salsabila; Dewi Trirahayu (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Work-Life Balance Analysis and Work-Life Analysis on the Performance of Employees of the Distributor Check-In and Check-Out Shipping Section at PT. AAA This study aims to examine the effect of Work-Life Balance and Work-Life Analysis on employee performance at the Distributor Shipping Check-In and Check-Out Unit of PT. AAA. This research employed a quantitative approach using a survey method. The population consisted of 35 employees, and a saturated sampling technique was applied, in which all members of the population were selected as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 27. The results indicate that Work-Life Balance has a positive and significant effect on employee performance, with a t-value of 4.189 and a significance level of < 0.001. Work-Life Analysis also has a positive and significant effect on employee performance, with a t-value of 3.404 and a significance level of 0.002. Simultaneously, Work-Life Balance and Work-Life Analysis have a positive and significant effect on employee performance, with an F-value of 67.060 and a significance level of < 0.001. The Adjusted R Square value of 0.795 indicates that both independent variables explain 79.5% of the variance in employee performance. Furthermore, Work-Life Balance was found to be the most dominant variable influencing employee performance.